The effect of banking sector competition on firm creation in Sub-Saharan Africa - Ramahuta, Katlego (University of the Witwatersrand, Johannesburg, 2025)
This study determines the effect of banking sector competition on firm creation in Sub- Saharan Africa (SSA). The study uses country-level data from multiple World Bank databases covering the period 2006-2021. While the analysis initially included all 48 SSA countries, only 40 countries were part of the final sample due to missing data in 8 countries. For a comprehensive view of the banking sector competition in the region, we use two non- structural measures of competition (Boone Indicator and the Lerner Index) and one structural measure (The concentration ratio calculated based on the top five banks, CR5). The Fixed Effects (FE) model and the two-step system Generalized Method of Moment (system-GMM) estimators are used to estimate the results of the analysis. Employing two estimators enhances robustness of the findings and ensures their consistency across different estimation techniques. Our findings support the market power hypothesis for SSA countries, indicating a positive relationship between banking sector competition and firm creation. This supports the view that increased competition in the banking sector will lead to an increase in the rate of firm creation. Based on the results, economic growth and higher levels of education lead to opportunities for firm creation. Our findings also show that new firm registration rates are lower in upper-income countries compared to lower-income countries in the region. The findings from this paper can inform policy decisions around banking sector competition regulation, and support initiatives that leverage firm creation as a tool to address unemployment and poverty in the region.
A research report submitted in fulfillment of the requirements for the Master of Economic Science, in the Faculty of Commerce Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Competition; firm creation; Boone Indicator; Lerner Index; Concentration Ratio; SDG-8: Decent work and economic growth